Analysis of Differences in Local Government Financial Performance Before and After Expansion on Papua Island - Ridha UL Halim; Desy Puspita (PT. Publikasiku Academic Solution, 2025)
Regional financial performance is an important indicator in assessing the effectiveness of financial management at the regional level. This study focuses on the comparison of the financial performance of Papua and West Papua Provinces before and after the division. This study aims to determine the differences in regional financial performance using various financial ratios after regional expansion in 2022. This research uses a descriptive qualitative approach with documentation as a data collection technique. The analysis was carried out through a comparison of the ratios of the degree of decentralization, dependence, independence, effectiveness of regional own-source revenue (PAD), and expenditure efficiency. The results showed that there were significant differences in the ratios of the degree of decentralization, dependency, independence, revenue effectiveness, and expenditure efficiency between Papua and West Papua Provinces before and after the division in 2022. The study concludes that pemekaran has affected regional financial performance, with changes in ratios reflecting higher dependence on central funds and decreased financial independence. This suggests the need for efforts to improve regional financial management capacity post-division.